Antinuclear antibodies define a subgroup of paraneoplastic neuropathies: clinical and immunological data. Issue 12 (16th November 2005) - Tschernatsch, M; Stolz, E; Strittmatter, M; Kaps, M; Blaes, F
Abstract : Objective: Paraneoplastic neuropathy is a clinical and immunological heterogeneous disorder and attempts have been made to classify subgroups of this disease. Only 30–50% of the clinical defined cases have antineuronal antibodies. Methods: The clinical and immunological features of 36 patients with paraneoplastic neuropathy from the authors' database were analysed including the type and course of the neuropathy, associated tumours, and the presence of antineuronal and other autoantibodies. Results: Antineuronal antibodies were detected in 17/36 patients (47%) and anti-Hu was the most frequent antineuronal antibody. Nine patients had high titre antinuclear antibodies (ANA, median titre 1/1000) without antineuronal antibodies. ANA reactivities were different in most patients. Comparison of the ANA positive and ANA negative patients revealed that ANA positive paraneoplastic neuropathy is more frequently associated with breast cancer but is not associated with lung cancer (p<0.05). The main clinical type in these patients was sensorimotor neuropathy. No ANA positive patient had central nervous system involvement. Although the Rankin score at the time of diagnosis was not different, the functional outcome in ANA positive patients was better than in ANA negative patients (p<0.05). Conclusions: Paraneoplastic neuropathy is a heterogeneous disorder. ANA may define a subgroup of paraneoplastic neuropathy with different clinical and immunological features and may be related to better prognosis of the neuropathic symptoms.